150 pre-participation cardiovascular disease screening, with or without an additional electrocardiogram and echocardiography, in potential recruits to the british army. (6th June 2015) - Cox, Andrew; Cannie, Douglas; Parson, Iain; Chamley, Rebecca; Behr, Elijah; Wilson, Duncan; Sharma, Sanjay; Burrows, Helen; Gardiner, Robert; Attwood, Julie
Abstract : Background: The British Army Initial Recruit Medical includes a history and physical examination. The study objective was to compare the incremental value of adding an electrocardiogram (ECG) and echocardiogram to this medical, in order to detect cardiac disease. Methods: A physical examination, ECG and echocardiogram were prospectively performed in volunteers when there was no history suggestive of cardiac disease. Electrocardiograms and echocardiograms were analysed according to published criteria. Further investigations were determined by clinical need. A pragmatic 'Gold standard' of ECG, echocardiogram and other investigations elsewhere, when clinically indicated, was used. Enlistment eligibility was decided using military guidelines. Results: 812 candidates volunteered. A murmur was detected in 73 (8.9%) candidates, 98 (12.1%) had an ECG abnormality and 161 (19.8%) had either a murmur or ECG abnormality. Sixteen candidates were diagnosed with disease on the day. Seventeen candidates (2.1%) required further cardiac investigations with disease ultimately excluded in sixteen (2.0%). Cardiac disease was detected in seventeen (2.1%) candidates with six conditions associated with sudden death in asymptomatic individuals. Thirteen (1.6%) candidates were prevented from enlisting. Diagnostic test evaluation: Physical examination only: Sensitivity: 52.94%, Specificity: 91.95%, Positive Predictive Value: 12.33%, Negative Predictive Value: 98.92%. Additional electrocardiogram: Sensitivity: 88.24%, Specificity: 81.53%, Positive Predictive Value: 9.26%, Negative Predicted Value: 99.69%. Conclusions: Adding an ECG to the Initial Recruit Medical is more sensitive in identifying disease than physical examination alone, but has a higher false-positive rate. When physical examination or ECG abnormalities are discovered additional echocardiography reduces the failure rate on the day to 4.1% and of these approximately half ultimately have a disease diagnosis.